Mathematical Model of Differential Equations to Population Growth Models with Limited Growth in West Nusa Tenggara Province - Robbaniyyah, Nuzla Af'idatur; Anjani, Mutia Dewi; Lansuna, Ni Wayan Eka; Ihwani, Ivan Luthfi (Eigen Mathematics Journal, 2024)
Differential equations are often a topic in the field of mathematics which has many applications in mathematical modeling, one of which is population growth. Research on population growth is of course important for an area because the results  of this research can be used in issuing policies such as maintaining the availability of agricultural land, places to live, and many others. In this study, the mathematical model of differential equations was used to find a population growth model for the West Nusa Tenggara Province, then the model was verified and calculations were carried    out using the Mathematica software. Then a model is generated with the equation (?) = 3504006 ?0,012(?−1993) which results in a calculation that the population of NTB will continue to grow so that it is necessary to verify the model which produces a logistics growth model.